Interactive Learning Multimedia Based Discovery Learning Mathematics Subject for Grade 4 Elementary School - Widnyana, I Made Dwi; Jampel, I Nyoman; Suartama, I Kadek (Journal of Educational Study, 2024)
This study was motivated by the low academic performance of fourth-grade elementary students in mathematics. The objectives were to: (1) design and develop interactive multimedia based on discovery learning, (2) evaluate the validity of the developed multimedia, and (3) assess its effectiveness in improving student learning outcomes. This research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. Data were collected through questionnaires and tests. Validity was assessed using a 4-point Likert scale and qualitative descriptive analysis of expert feedback on content, design, and media, as well as student responses through individual trials (3 students) and small group trials (9 students divided into 3 groups). Effectiveness was tested using a pretest-posttest design involving 20 fourth-grade students, analyzed with a t-test. Results indicated the multimedia was valid according to experts (85.93%–95%) and received positive responses from students (87.38%–87.73%). The t-test showed significant improvement in learning outcomes. The findings imply that discovery learning-based interactive multimedia is effective in enhancing students' mathematical understanding.